'I don't think I'd be frightened if the statins went': a phenomenological qualitative study exploring medicines use in palliative care patients, carers and healthcare professionals. Issue 1 (December 2016) - Todd, Adam; Holmes, Holly; Pearson, Sallie; Hughes, Carmel; Andrew, Inga; Baker, Lisa; Husband, Andy
Abstract Background There is a growing body of evidence suggesting patients with life-limiting illness use medicines inappropriately and unnecessarily. In this context, the perspective of patients, their carers and the healthcare professionals responsible for prescribing and monitoring their medication is important for developing deprescribing strategies. The aim of this study was to explore the lived experience of patients, carers and healthcare professionals in the context of medication use in life-limiting illness. Methods In-depth interviews, using a phenomenological approach: methods of transcendental phenomenology were used for the patient and carer interviews, while hermeneutic phenomenology was used for the healthcare professional interviews. Results The study highlighted that medication formed a significant part of a patient's day-to-day routine; this was also apparent for their carers who took on an active role-as a gatekeeper of care-in managing medication. Patients described the experience of a point in which, in their disease journey, they placed less importance on taking certain medications; healthcare professionals also recognize this and refer it as a 'transition'. This point appeared to occur when the patient became accepting of their illness and associated life expectancy. There was also willingness by patients, carers and healthcare professionals to review and alter the medication used by patients in the context of life-limiting illness. Conclusions There is a need to develop deprescribing strategies for patients with life-limiting illness. Such strategies should seek to establish patient expectations, consider the timing of the discussion about ceasing treatment and encourage the involvement of other stakeholders in the decision-making progress.